Distribution and morphological variation of Stelechocarpus burahol in Java, Indonesia - ARTINA ATRI NORANTIN; NINA RATNA DJUITA; SULISTIJORINI SULISTIJORINI (Society for Indonesian Biodiversity, 2025)
Abstract. Norantin AA, Djuita NR, Sulistijorini. 2025. Distribution and morphological variation of Stelechocarpus burahol in Java, Indonesia. Biodiversitas 26: 4284-4296. Stelechocarpus burahol is a species historically used in Java as a natural perfume. Understanding its distribution and morphological variation is crucial for conservation given its rarity. This study aimed to provide the first island-wide distribution mapping and the first morphological analysis of S. burahol in Java. Field surveys in 16 districts across West, Central, and East Java yielded 54 accessions, collected using exploratory sampling method with geographic coordinates recorded to generate a distribution map. A total of 51 morphological characters from both vegetative and generative organs were observed and analyzed using Unweighted Pair Group Method with Arithmetic Mean (UPGMA) in NTSYS 2.02i, Principal Component Analysis (PCA), and Pearson correlation analysis in RStudio 2023.12.1. Field observations revealed that S. burahol remains relatively abundant in Kebumen, Purworejo, Blitar, and Meru Betiri National Park. S. burahol exhibits variation in the shape of the canopy, leaves, flower petals, fruits, and seeds. Phenetic analysis grouped accessions into three major clusters: Group I (25 accessions, small subglobose fruits), Group II (27 accessions, medium obovoid fruits), and Group III (2 accessions, large obovoid fruits). These clusters did not correspond to geographic origin, indicating that phenotypic similarity primarily influences morphological variation. PCA confirmed that fruit traits, particularly fruit length, diameter, weight, and flesh weight (eigenvalues > 0.9), were dominant in group separation. Pearson correlation revealed a relationship among key fruit traits. These findings provide baseline data to support future conservation efforts, with priority given to Group III's large-fruited accessions and Group I's forest-associated populations.